Synthesis and Antibacterial Screening of New Schiff Bases Based on N-(4-acetophenyl) Succinimide - Marouf Al-Azzawi, Ahlam; Abd Al-Kareem Raheem, Ali (Iraqi Journal of Science, 2021)
A series of nine new Schiff bases based on N-(4-acetophenyl)succinimide were synthesized via multistep synthesis. In the first step N-(4-acetophenyl)succinamic acid was prepared via reaction of succinic anhydride with 4-aminoacetophenone. The prepared amic acid was dehydrated in the second step producing N-(4-acetophenyl)succinimide. The prepared succinimide represents a modified methyl ketone bearing succinimde cycle and ready for introducing in condensation reaction thus in the third step the prepared imide was introduced in acid-catalyzed condensation reaction with a variety of primary aromatic amines affording the new target Schiff bases. The results of antibacterial screening of the newly synthesized Schiff bases indicated that they possess high antibacterial activity.